Small Area Estimation for Per Capita Expenditure in Sulawesi Selatan using Empirical Best Linear Unbiased Prediction - Miolo, Alya Safira Irtiqa; Sunusi, Nurtiti; Siswanto, Siswanto (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2024)
Small area estimation (SAE) is an important technique for estimating parameters in regions or sub-populations with limited sample sizes, particularly when direct estimators are inadequate in capturing area-specific information. The Empirical Best Linear Unbiased Prediction (EBLUP) method is one of the SAE parameter estimation approaches, aiming to minimize Mean Square Error (MSE) by incorporating unknown variations of components. In this research, we derive an SAE model parameter estimator and compare its outcomes with both the direct estimator and EBLUP-SAE. The dataset used in this study consists of per capita expenditure data obtained from the March 2019 National Socioeconomic Survey (Susenas) conducted in South Sulawesi, providing a benchmark for assessing household purchasing power. The estimation of SAE parameters was performed using the maximum likelihood method. The results using the EBLUP method reveals that Makassar City recording the highest per capita expenditure at Rp.1,206,352.79 and Jeneponto Regency with the lowest at Rp.1,000,887.29, reflecting significant disparities. Furthermore, the estimated variance of random influence was determined to be 0.010. The study's findings indicate that the EBLUP method outperforms the direct estimation method in estimating per capita expenditure. This is evidenced by the significantly lower MSE value of the EBLUP method, averaging 0.001, compared to the direct estimator’s average MSE value of 0.002. The finding not only emphasizes the reliability of the EBLUP method but also enhances the robustness of socioeconomic analyses and contributes to the advancement of small area estimation techniques. This provides a novelty in understanding regional disparities and informing policy decisions.Keywords: small area estimation, direct estimation, EBLUP, per capita expenditure. AbstrakSmall area estimation (SAE) merupakan metode yang digunakan untuk menduga parameter yang berasal dari area atau sub populasi dengan ukuran sampel yang kecil, ketika estimasi menggunakan penduga langsung tidak mampu menyampaikan informasi area terkait. Metode Empirical Best Linear Unbiased Prediction (EBLUP) merupakan salah satu metode estimasi parameter SAE yang meminimumkan Mean Square Error (MSE) yang dihasilkan dengan asumsi komponen ragam yang tidak diketahui. Penelitian ini bertujuan untuk memperoleh estimator parameter model SAE dan memperoleh perbandingan hasil penduga langsung dan EBLUP-SAE. Data yang digunakan dalam penelitian ini yaitu data pengeluaran per kapita berdasarkan hasil Survei Sosial Ekonomi Nasional (Susenas) Maret 2019 di Sulawesi Selatan, yang berfungsi sebagai tolak ukur untuk menilai kekuatan beli rumah tangga. Estimasi parameter SAE dilakukan menggunakan metode maximum likelihood. Berdasarkan metode EBLUP, diperoleh bahwa nilai pengeluaran per kapita terbesar terjadi di Kota Makassar, yaitu sebesar Rp.1,206,352.79, sedangkan nilai pengeluaran per kapita terkecil terjadi di Kabupaten Jeneponto, yaitu sebesar Rp.1,000,887.29, mencerminkan disparitas yang signifikan. Sementara itu, diperoleh nilai estimasi varians dari pengaruh acak sebesar 0.010. Hasil estimasi dari penelitian ini menunjukkan bahwa metode EBLUP lebih baik dalam melakukan estimasi pengeluaran per kapita dibandingkan metode penduga langsung. Hal ini ditunjukkan dengan nilai MSE dari metode EBLUP menghasilkan rata-rata nilai MSE yang lebih kecil, yaitu sebesar 0.001 dibandingkan dengan rata-rata nilai MSE penduga langsung, yaitu sebesar 0.002. Hal ini tidak hanya menekankan reliabilitas metode EBLUP tetapi juga meningkatkan ketangguhan analisis sosial ekonomi dan berkontribusi pada kemajuan teknik estimasi area kecil. Hal ini memberikan kebaruan dalam pemahaman disparitas regional dan pengambilan keputusan kebijakan.Kata Kunci: small area estimation, penduga langsung, EBLUP, pengeluaran per kapita. 2020MSC: 62J05